The acquisition of sociolinguistic competence in a study abroad context [ - Regan, Vera; Howard, Martin , 1972-; Lemaee, Isabelle , 1968- (Second language acquisition, 2009)
Drawing on cross-sectional and longitudinal analyses of a range of sociolinguistic variables in L2 French, this volume explores the relationship between 'study abroad' and the acquisition of sociolinguistic variation patterns by the advanced second language learner.